Study of the quality of life 6 months post intensive care unit discharge in abdominal surgery patients - Siew, Teo Saint (2018)
With increasing cost of intensive care and limited resources, quality of life assessment post intensive care may provide insight regarding which group of patients will benefit most for intensive care. The objective of the study wais to determine quality of life 6 months post Intensive Care Unit discharge and its associated factors that affect it in surgical patient. This was a retrospective prospective observational study conducted in Intensive Care Unit inof Hospital Universiti Sains Malaysia between January 2016 to December 2016. WHOQoL-BREF questionnaire wasere used in this study. Results showed that as total of 52 participants were recruited, with mean age 54±19 years old and slightly more male (55.8%) than female (44.2%) participants. The mean percentage scores of the four domains (physical, psychological, social, environmental domains) were above 60%. SubjectsAge above 60 years old revealed lower mean score in all four domains inof the WHOQoL-BREF questionnaire. F While female gender and SAP scores more than 29 have lower than mean score in social relationship domain. The conclusion of this study is that age playsis a significant factor in the reduced quality of life post ICU discharge in post abdominal surgery patient.